ANALYSIS OF JUDGE DECISION NUMBER 1537/Pid.B/2016/PnJkt.Utr RELATED TO PENAL CODE AGAINST BLASPHEMY PERPETRATOR - Achmad Arif; Haerul Akmal; Muhammad Imam Subagja (IAIN Bone, 2021)
The discourse on religious blasphemy is one that raises a lot of polemics. In the Indonesian context, this does not only occur in the domain of positive law, but also extensively in the domain of Islamic thoughts. The underlying issue of the argument is whether the penalty to whom blaspheme such a religion in accordance of the satisfaction and teaching of every adherent of religion in Indonesia, such types of questions emerge in discussions regarding the matter of what is most relevance in accordance of the teachings of the defied religion which in this case is Islam. This research aims to find out the sanctions imposed by the judge in case No.1537/Pid.B/ 2016/ PN. JktUtr. according to the perspective of Islamic law and also the law in force in Indonesia so that the normative juridical approach method used with logical thinking is deductive.